The Relationship between Headteachers’ level of Integration of computers in the Management of Curriculum in Secondary Schools and their Personal Characteristics - Mulwa, David Musyoki; Kimosop, Maurice Kibet (International Journal of Education and Research, 2015)
The purpose of this study was to establish the relationship between headteachers’ level of integration of computers in the management of curriculum in secondary schools and their personal characteristics in Nandi and Uasin Gishu counties of Kenya. The study employed the descriptive survey research design. A total of 63 headteachers’ from 63 schools with functional ICTs were purposively selected. The data was collected by use of a questionnaire. Data was analysed by the use of Pearson Correlation and Multiple Regression Analysis. A significant relationship was found between the age of the headteacher, administrative experience and ICT training, and the level of integration of computers. Gender and academic qualification were found not to be significantly related to level of ICT intergration. It is hoped that the study will benefit education policy makers and headteachers in adopting effective ICT integration strategies in secondary schools
Keywords: Personal Characteristics; ICT Integration; Curriculum